Activated carbon materials-derived from polyethylene terephthalate (PET) plastic waste using H3PO4 activation for Rhodamine B removal in aqueous solution - Le Minh Tri (Journal of Military Science and Technology, 2024)
Plastic items, which offer convenience, are ubiquitous in several manufacturing sectors and in everyday life. Polyethylene terephthalate (PET) is a highly popular synthetic plastic that is seeing a growing demand. Annually, a substantial quantity of PET plastic garbage is released into the environment. Hence, it is imperative to devise an efficient remedy for the disposal of PET plastic waste. This work employed PET waste plastic to produce activated carbon by the chemical activation method. The activating agent utilized was H3PO4 acid. An investigation was conducted to determine the impact of the impregnation rate of PET waste plastic with H3PO4, as well as the activating temperature and activating time, on the surface areas of activated carbon. The activated carbon was thoroughly analyzed using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET) analysis. The resulting product has a porous structure, a developed pore system, and a specific surface area of 892 m2/g, with effective adsorption capacity for RhB solutions with concentrations below 80 ppm (efficiency above 90%) in a neutral environment according to the Langmuir adsorption isothermal model, with a maximum adsorption capacity of 45.45 mg/g.